Social networks, social support, and life expectancy in older adults: the Cardiovascular Health Study. - Bhatia, Roma; Hirsch, Calvin; Arnold, Alice M; Newman, Anne B; Mukamal, Kenneth J (Arch Gerontol Geriatr, 2023)
BACKGROUND: Social support and social networks have long been postulated to impact health outcomes but their impact on life expectancy and disability in older adults remains poorly quantified. METHODS: As part of the Cardiovascular Health Study, we followed 5,749 adults aged 65 years and older from 4 US field centers for 25 years. We assessed the Lubben social network score [range 0-50] and a social support score [range 0-24] derived from the Interpersonal Support Evaluation List (ISEL-12) in two consecutive years starting at study recruitment. We used remaining years of life (YOL) from study enrollment to death to approximate life expectancy. We defined years of active life (YAL) as the number of study years in which participants lived without any difficulties in activities of daily living. We used compression of disability to reflect the proportion of life lived able (YAL/YOL). We used linear regression to adjust for socio-demographics and comorbidity. RESULTS: The mean (standard deviation [SD]) scores were 32.3 ± 6.8 points for social network score and 8.3 ± 2.4 points for social support score. For every 1-SD increase in social network score, adjusted participant life expectancy was 0.40 years higher (95% CI 0.22-0.58; p<0.0001) and disability-free life expectancy 0.35 years higher (95% CI 0.18-0.53; p<0.0001). The association with life expectancy was modified by participant age (p<0.001), but it remained significant even among participants aged ≥75 years (3 months per SD; 95% CI 0.1-6 months, p = 0.04). Further adjustment for frailty did not attenuate the estimates. The social support scale was not significantly associated with YOL or YAL after adjustment for social network score, and neither measure was associated with compression of disability. DISCUSSION: In older adults, higher social network scores are significantly associated with longer life expectancy and disability-free life expectancy.